Financing Risk Management: Maq??id Mukallaf Review of Islamic Banks’ Financing Analysis - Yulia Yulia; S Purnamasari; Naili Rahmawati (Journal of Islamic Economy and Business (JIsEB), 2023)
This study aims to examine if the financing analysis carried out by Islamic banks in an effort to avoid financing risks is in accordance with qa?du al-sh?ri' (the Lawgiver’s intent) and qa?du al-mukallaf (the obligee’s intent). The methods used in this study were comparative approach and conceptual approach. This study found that financing risk management aims to achieve the common good, namely avoiding the risk of non-performing financing that can harm various parties in accordance with the purpose. Based on this analysis, there is a conformity between the objectives and intention of the oblige (maq??d al-mukallaf) which are in accordance with sharia (maq??d shar?'). This can be accepted in terms of Maq??id al-shar?’ah (higher objectives of sharia) because the risk management performed and the objectives of the Islamic bank as the mukallaf (obligee) are consistent. This study recommends that Islamic banks should be stricter in conducting financing risk management to achieve the public interest.